Murabaha contract for the purchase orderer between Sharia controls and field applications - Ghouini, Samir; Madji, Abdelmadjid (The International tax journal, 2025)
In this research paper, we addressed one of the most important Islamic financing contracts used by most Islamic banks, namely the Murabaha contract for the buyer's order. We clarified the difference between the Sharia-compliant Murabaha and the Murabaha for the buyer's order as practiced by Islamic banks today. We also highlighted the main criticisms of this contract and outlined the regulations that must be adhered to in order to avoid all the Sharia violations identified by scholars and jurisprudential assemblies, which in turn pose a risk that prevents clients from accepting and relying on it in their transactions.